Nasal carriage of Staphylococcus aureus and Candida species in immunocompetent individuals - Nastri, María L. (2012)
The aim of this study was to analyze the prevalence of Staphylococcus aureus and Candida species in samples of nasal mucosa from 100 immunocompetent subjects of both sexes, aged 18-70 years, during stomatological clinical examination. Samples were taken from the mucosa of both nasal fossae using sterile swabs.Samples were observed fresh, stained with Gram and Giemsa, and cultured on selective differential media at 37ºC to isolate and identify the selected microorganisms; conventional biochemical tests and comercial equipment and molecular studies using PCR were performed. A digital thermometer-hygrometer was used to measure room temperatura at the time of sampling, which was on average 25±2o C, with relative ambient humidity 66±11%. S. aureus was isolated from 38% of the samples; 4% of the samples were methicillin-resistant (MRSA) strains, with 2% identified genetically as community-acquired (CA-MRSA) and 2% as hospital-acquired (HA-MRSA). Candida was identified in 23% of the samples, with prevalence of C. albicans (19%) followed by C. dubliniensis (3%) and C. krusei (1%). There was significant association between Candida and S. aureus (Chi-squared = 27.75; df = 1; (p<0.001). The nasal cavity is a reservoir and the identification of genus and species contributes to adequate epidemiological surveillance.